TEACHERS’ PERSPECTIVE ON THE MACAO EDUCATION REFORM POLICY - TCHIANG, Van (PEOPLE: International Journal of Social Sciences, 2017)
The paper presents an overview to understand the perceptions, reflections, opinions and perspectives of pre-service and in-service teachers in Macao local schools in respect to policies and plans introduced by the Macao government department, the Education and Youth Affairs Bureau (DSEJ). The DSEJ had been working on the Macao Education Reform since 2011, and the Ten Year Plan for the Development of Non-Tertiary Education was in progress accordingly. Various policies and actions continued to proceed in accordance with the Macao Education Reform. The paper examines the situation through the lenses of teachers’ perceptions regarding the success and effectiveness of these policies introduced by the government department in MacaoThe study followed a mixed methods approach, utiliing detailed information from interviews with pre-service and in-service teachers followed by a survey. The initial phase of the study aimed to identify the range of different beliefs and attitudes towards the plans and policies introduced by the government department in Macao. The results from this initial phase were then used to develop a survey which was administered to a larger sample of pre-service and in-service school teachers from various types of school. The data were used to quantify the extent to which different beliefs and attitudes towards the various plans and policies introduced by DSEJ were endorsed by teachers in Macao. The results of the study provide valuable information on the extent to which Macao teachers agree on the new policies introduced by DSEJ; whether there is any difference in respect of pre-service and in-service teachers; what teachers’ perceptions are of the positives and negatives of the policies; and how effective the policies introduced by the government department in Macao are.